WOMEN EMPOWERMENT THROUGH MNREGA: EMPOWERMENT OF WOMEN IN RURAL AREAS - Yadav, Mahadeo Chandra (International Journal of Research -GRANTHAALAYAH, 2025)
This study presents a comprehensive analysis of the role of Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) in empowering rural women. MNREGA was launched with the objective of increasing livelihood security, employment opportunities and social inclusion in rural areas. The scheme mandates women to constitute one-third of the workforce, guarantees equal pay, and provides crèches and other facilities at workplaces. The study shows that MNREGA has provided women with the opportunity to become economically self-dependent, thereby increasing their financial awareness and participation in family decisions. At the same time, the scheme challenges the limited definitions of traditional ‘empowerment’ by treating women as partners in development and not as objects of assistance. However, in reality, many social, cultural and administrative barriers limit the full potential of the scheme. Women's economic participation has increased, but their decision-making role in the home and society still remains limited. This study highlights the paradox that despite the availability of economic opportunities, social structures continue to hinder women's real empowerment.